"Lezibian/mulezi": adoption of "globalized" lesbian identity and secondary self-labels among same-sex attracted women in Harare. Issue 3 (3rd July 2022) - Muparamoto, Nelson
Abstract: Drawing from ethnographic research, incorporating informal conversations, semi-structured interviews and a focus group discussion, the paper explores the subjective meanings and construction of the "lesbian" identity in a "hostile" environment among selected same-sex attracted women in Harare. While the globally circulating identity labels are loaded with historical baggage which can be limiting or confusing in non-western contexts, most of the study participants related to some of the labels that are prominent in the present-day, western-inspired global discourse on same-sex relations. Self-styling and the quest to exhibit masculine decorum was a central aspect in the narratives of most "butch" identifying women. For most butch identifying women being lesbian was closely interwoven with considerations about one's gendered self. However not all participants were comfortable with the circulating identity labels as they found them restrictive and loaded. While subjective preferences of the participants demonstrate complexity in how "lesbianism" is locally constructed and experienced, the lesbian identity is certainly not obsolete in Harare among same-sex attracted women.